On the assessment of multiaxial fatigue damage under variable amplitude loading (Fracture and Structural Integrity, 2016)
In this work, the performance of the SSF criterion is evaluated under variable amplitude loading conditions. The main objective was to inspect the validity of the hypothesis in which the SSF damage map remains valid for any high strength steel. In order to achieve that, fatigue life correlation of the 1050QT steel and 304L stainless steel was analyzed under multiaxial loading conditions. The loading block considered in the study comprises 360 proportional loading cycles with different stress amplitude ratios and stress levels. Despite being made of proportional branches, this loading block is a non-proportional loading due to its principal directions variation. This feature allows the evaluation of combined loading effects under variable amplitude loading conditions, which makes this loading block suitable to mimic the loading effects usually found in the field. Results show very good agreements, which reinforces the aforementioned hypothesis
Keywords: Multiaxial fatigue; Variable amplitude loading; Multiaxial cycle counting method; Fatigue life; Damage accumulation